Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1592/phco.20.19.1508.34852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Impact of Ambulatory Care Clinical Pharmacists in Management of Dyslipidemia in Older Adults: The IMPROVE Study

Abstract: We examined the impact of ambulatory care clinical pharmacist interventions on clinical and economic outcomes of 208 patients with dyslipidemia and 229 controls treated at nine Veterans Affairs medical centers. This was a randomized, controlled trial involving patients at high risk of drug-related problems. Only those with dyslipidemia are reported here. In addition to usual medical care, clinical pharmacists were responsible for providing pharmaceutical care for patients in the intervention group. The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 26 publications
2
94
0
2
Order By: Relevance
“…Interventions that include a pharmacist working in conjunction with the treating physician have been successful in attaining lipid goals in other settings and may be one promising approach for patients with diabetes managed in primary care. [25][26][27][28] Our results are similar to findings reported in the Lipid Treatment Assessment Project (LTAP), a study of 4888 patients with dyslipidemia. 15 In the LTAP study, only 38% of adult patients with dyslipidemia achieved the LDL goal specified by the National Cholesterol Education Program (NCEP).…”
Section: Discussionsupporting
confidence: 87%
“…Interventions that include a pharmacist working in conjunction with the treating physician have been successful in attaining lipid goals in other settings and may be one promising approach for patients with diabetes managed in primary care. [25][26][27][28] Our results are similar to findings reported in the Lipid Treatment Assessment Project (LTAP), a study of 4888 patients with dyslipidemia. 15 In the LTAP study, only 38% of adult patients with dyslipidemia achieved the LDL goal specified by the National Cholesterol Education Program (NCEP).…”
Section: Discussionsupporting
confidence: 87%
“…[168][169][170] In addition, only seven studies reported one or more centre-specific characteristics such as the volume of cases they treat. 166,[173][174][175][176]196,197 These results are perhaps as expected, and it can be argued that authors would not normally be expected to provide such information. However, any reasonable assessment of the extent to which results found in a combination of locations apply to a particular location (within or outside the trial) requires information on what types of centres were included in a study and how trial patients compare with non-trial patients.…”
Section: Study Reportingsupporting
confidence: 59%
“…Numerous studies in settings such as Veterans Affairs clinics, community pharmacies, and indigent programs have shown that pharmacists can increase patient adherence to therapy, achieve reductions in total and low-density lipoprotein cholesterol levels, and increase the proportion of patients achieving recognized treatment goals with increased patient satisfaction and at minimal cost. [40][41][42][43][44][45][46] The importance of clinical pharmacists in the care of patients with heart failure has been described recently. 47 Pharmacists also have been successful in providing health care and drug assistance to underserved individuals, often using manufacturer-sponsored drug assistance programs.…”
Section: Pharmacy Implications Of Healthy People 2010 Accp Primary Carementioning
confidence: 99%
“…A multicenter study of pharmacist provision of pharmaceutical care from Veterans Affairs medical centers showed significant improvement in total and low-density lipoprotein cholesterol values compared with standard care. 43 Rates of persistence and compliance with drug therapy were more than 90% in an observational study of 26 community pharmacies providing pharmaceutical care for patients with hypercholesterolemia. 41 Pharmacists in the hospital setting are successful in working with teams to get appropriate patients tested and treated for secondary prevention of heart disease.…”
Section: Cholesterolmentioning
confidence: 99%